Web-Based ERP Dashboard Integrated with Aerial Imagery for Oil Palm Harvest Monitoring and Plantation Decision Support - M. Ilham Saputra; Raden Aris Sugianto; Andi Prayogi; Febriani Putri Wulandari (Academic Bright Collaboration, 2026)
Purpose – Oil palm plantation operations often rely on fragmented reporting systems that hinder information synchronization, operational visibility, and monitoring effectiveness. This study aims to develop a web-based Enterprise Resource Planning (ERP) dashboard integrated with Geographic Information System (GIS) mapping and aerial imagery visualization to support harvest scheduling and operational monitoring. Methods – This study employed a Research and Development (R&D) approach using the System Development Life Cycle (SDLC), including requirement analysis, design, implementation, testing, and evaluation. The system was developed using Laravel, MySQL, Bootstrap, and Leaflet GIS. Usability evaluation was conducted based on the ISO 9241-11 framework involving 11 participants consisting of plantation managers, field assistants, supervisors, and administrative staff at PT. Gerbang Benuaraya. Findings – The developed system successfully integrated operational reporting, plantation block mapping, aerial imagery visualization, and harvest monitoring within a centralized dashboard. Usability evaluation produced effectiveness, efficiency, satisfaction, learnability, and memorability scores of 72.12%, 69.70%, 72.12%, 65.45%, and 70.91%, respectively, resulting in an overall usability score of 70.06%, which indicates good usability based on the percentage-based evaluation criteria applied in this study. Research implications – The findings suggest that the system can support operational monitoring and information integration in plantation environments. However, the evaluation was conducted in a single plantation company with 11 participants, limiting broader generalization. Originality – This study contributes an integrated platform that combines ERP operational modules, GIS-based plantation mapping, aerial imagery visualization, and harvest monitoring within a single dashboard specifically designed for oil palm plantation management.